Latin America and the Caribbean standard operating procedure for the analysis of cadmium in cacao - Lewis, Caleb (Inter-American Institute for Cooperation in Agriculture (IICA), 2024)
The protocols and procedures are routinely used by the project implementing agencies and documented as Standard Operating Procedures (SOPs) in this manual. The SOPs are for use by technicians in the routine analysis of Cd throughout the Latin America and Caribbean (LAC) region. These SOPs can be used by laboratories throughout the LAC region to support cacao farmers and the Cocoa Value Chain to ensure beans meet the regulations for levels of Cd in cocoa and chocolate products adopted by the European Food Safety Authority and Codex Alimentarius. The procedures and protocols have been validated for analysing Cd in soils and cocoa solids only. The procedures and protocols for measuring Cd content using the GFAAS, ICP-MS, ICP-OES and the emerging E-maxTM instruments are detailed in this manual.